DHARMAGĪTĀ: NYANYIAN KEAGAMAAN HINDU “SEKAR MADYA” BERBASIS APLIKASI MULTIMEDIA INTERAKTIF: Nyanyian Keagamaan Hindu “Sekar Madya” Berbasis Aplikasi Multimedia Interaktif - Prayoga, I Made Ade; Eka, Putu Eka Sura Adnyana (Sphatika: Jurnal Teologi, 2025)
Sekar madya is sung in groups of more than two people simultaneously without the process of translating the contents of the song text. The introduction of sekar madya still uses media in the form of books so that people cannot have it instantly and the interest generated does not last consistently, therefore an interactive introduction media is needed that can be utilized by the people in Bali. The design of the Sekar Madya Voice Art Introduction application is in accordance with the research method used, namely the Multimedia Development Life Cycle (MDLC) method. This method consists of six stages, namely concept (concept creation), design (design/draft), material collecting (material collection), assembly (compilation/creation), testing (testing) and distribution (dissemination). First, a mobile-based sekar madya introduction application has been produced using the MDLC method to preserve the tradition of reading Hindu literature and Balinese culture. Second, this application is used as a medium for introducing sekar madya but can also be used to document cultural heritage in digital form. Third, this multimedia application has been successfully built using Adobe Flash Professional Cc with the Action Script 3.0 programming language as the creation of programs and animations, while for the design using Corel Draw X7, then for video and audio editing using Adobe Premiere. And fourth, Based on system testing using the black box testing method, the results of the test show that the functionality of the system created is in accordance with the needs analysis and system design.